Impact of hot-air and infrared-assisted solar drying on the drying characteristics and physicochemical properties of cacao beans (Theobroma cacao L.) - Baldeón, Edwin O.; Mamani-Olgado, Lizbeth R.; Silva-Santisteban, Bernardo O. Yépez; Chire-Fajardo, Gabriela C.; Martínez-Guerrero, Nubia C.; Ureña-Peralta, Milber O. (Frontiers in Sustainable Food Systems, 2025)
Cacao beans are essential components of chocolate production, and their quality is due to the formation of aromas and flavors during fermentation and drying processes. This study aimed to characterize the drying process and analyze the physicochemical properties of fermented and dried cacao beans using hot-air and infrared-assisted solar drying. Fermentation was performed in a portable fermenter and drying was performed using four methods: solar (S), hot-air-assisted solar (HA-S), infrared-assisted solar (IR-S), and hot-air- and infrared-assisted solar (HA-IR-S). The drying rate, effective moisture diffusivity, energy consumption, bean dimensions, acidity, pH, and cut test results were evaluated. The results showed the influence of the HA-IR-S method on the drying rate compared to the S method, as the assisted drying system increased the temperature of the cacao bean by 3.8°C, resulting in an increase in the effective diffusivity of 3.4% (1.22 × 10−9 m2/s). The HA-IR-S method achieved a drying effect similar to that of the HA-S method but with lower energy consumption. Significant differences were found in the physicochemical properties between the solar and assisted solar methods, with the HA-IR-S method showing the lowest acidity and pH, thus improving the degree of bean fermentation. In conclusion, the drying of cacao beans using solar energy with hot air and infrared radiation has been shown to improve their drying characteristics and physicochemical properties. This development constitutes a viable alternative for improving the drying efficiency and quality of beans.